2008
DOI: 10.1186/1471-2202-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Neural markers of a greater female responsiveness to social stimuli

Abstract: Background: There is fMRI evidence that women are neurally predisposed to process infant laughter and crying. Other findings show that women might be more empathic and sensitive than men to emotional facial expressions. However, no gender difference in the brain responses to persons and unanimated scenes has hitherto been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
82
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 49 publications
14
82
0
1
Order By: Relevance
“…Additionally, we found this asymmetry in an 601 earlier ERP component (P1) than has previously been studied (N170; 602 increased LPC response to all stimuli types, relative to men, although this 616 difference did not reach statistical significance at all time windows. However, 617 this pattern is consistent with work demonstrating that women show increased 618 responsivity to social stimuli, generally (Proverbio et al, 2008). Overall, our results demonstrate a preferential response to infant faces in 637 early and late processing stages that is independent of the aesthetic quality of 638 the face or observer sex, providing additional evidence for a "baby specific" 639 neural response (e.g., Kringelbach et al, 2008).…”
Section: ) 525 526supporting
confidence: 80%
“…Additionally, we found this asymmetry in an 601 earlier ERP component (P1) than has previously been studied (N170; 602 increased LPC response to all stimuli types, relative to men, although this 616 difference did not reach statistical significance at all time windows. However, 617 this pattern is consistent with work demonstrating that women show increased 618 responsivity to social stimuli, generally (Proverbio et al, 2008). Overall, our results demonstrate a preferential response to infant faces in 637 early and late processing stages that is independent of the aesthetic quality of 638 the face or observer sex, providing additional evidence for a "baby specific" 639 neural response (e.g., Kringelbach et al, 2008).…”
Section: ) 525 526supporting
confidence: 80%
“…Yet, we observed an activation of left EBA, which has been reported to be involved in the imagery of human bodies, whereas the right EBA is more commonly involved in the visual perception of human bodies (Downing et al 2007;Aleong and Paus 2010;Proverbio et al 2008). Thus, if the attention would have interfered with the present EBA activation, it should have rather influenced right EBA, which is not the case.…”
Section: Extrastriate Cortexmentioning
confidence: 50%
“…Although the lateralization of EBA's activity in response to visual bodily stimuli is still an open debate, no lateralization was observed in some previous fMRI work (Grossman and Blake 2002;Saxe and Kanwisher 2003;Astafiev et al 2004;Hodzic et al 2009a), whereas a differential EBA lateralization was observed when bodily identity and action discrimination were tested (Hodzic et al 2009b;Urgesi et al 2007). Other fMRI studies found greater consistency (Downing et al 2001) and selectivity (Downing et al 2006a;Downing et al 2006b) for the right EBA or a general greater whole-body selectivity in the right versus left EBA (Downing et al 2007;Aleong and Paus 2010;Proverbio et al 2008). Our results at the level of the EBA are in agreement with results of a previous study that also investigated mental imagery of full human body stimuli (Zacks et al 1999) and reported bilateral activations near the EBA with a left hemisphere predominance.…”
Section: Extrastriate Cortexmentioning
confidence: 92%
“…To ascertain that neuronal generators triggered two separate P3 components, topographical voltage maps of the scalp-recorded data were realized by plotting color-coded isopotentials derived by interpolating voltage values between scalp electrodes at specific latencies (Proverbio et al, 2008). An improved version of standardized Low Resolution Electromagnetic Tomography incorporating a singular value decomposition-based lead field weighting (swLORETA) was used to estimate intracranial sources of the scalp-recorded data (Nazari et al, 2010;Palmero-Soler et al, 2007;Pascual-Marqui et al, 1994).…”
Section: Brain Electric Tomographymentioning
confidence: 99%